The relationship between hemodialysis patients’ treatment adherence, procrastination, and difficulty in emotion regulation: A cross-sectional study in southeast Iran - Bazrafshan, Fateme Dahaghin; Darvizeh, Zahra; Banijamali, Shokoh Sadat (Frontiers in Psychology, 2023)
Background: End-stage renal disease is a life-threatening condition in which patients require dialysis or kidney transplant. These patients must adhere to the treatment regimen because treatment non-adherence affects their quality of life and health. We conducted this study to predict hemodialysis patients’ treatment adherence based on procrastination and difficulty in emotion regulation. Materials and methods: We conducted this descriptive correlational study on 218 hemodialysis patients with chronic kidney disease. We used purposive sampling to select participants from six dialysis centers in Kerman, Sirjan, and Rafsanjan. The measuring tools included the end-stage renal disease adherence questionnaire, general procrastination scale, decisional procrastination scale, and difficulty in emotion regulation scale. We used the correlation coefficient, regression analysis, and SPSS18 to analyze data. Results: Our study indicated that among the dimensions of treatment adherence, medication use had a significant, weak, and inverse relationship with general and decisional procrastination. We also found a significant, weak, and inverse relationship between attendance and general procrastination (P<0.05 and P<0.01). But there is no significant relationship between treatment adherence, general procrastination, and decisional procrastination (P>0.05). Multivariate regression analysis revealed a relationship between age, the cause of kidney failure, and treatment adherence (P=0.01 and P=0.02). Conclusion: Treatment non-adherence causes problems and complications in hemodialysis Patients, and disrupts their course of treatment. Therefore, it is necessary to identify the factors influencing non-adherence of patients undergoing hemodialysis and improve their treatment adherence, and thus their quality of life.